Socio-Spatial Disparities in Environmental Health in the City of Johannesburg - Nyangule, Zizipho (University of the Witwatersrand, Johannesburg, 2024)
This research explored socio-spatial disparities in environmental health within the urban context of Johannesburg, specifically focusing on access to environmental health services in both low- income and high-income neighborhoods. The study aimed to comprehend how disparities in access to essential services impact residents' environmental health experiences. Employing a qualitative research methodology, data was collected from two focus groups as part of the Sustainable, Healthy, Learning Cities and Neighborhoods (SHLC) project. A hybrid thematic analysis approach was utilized to examine secondary data from focus groups conducted in both low-income and high- income neighborhoods, illuminating the unique challenges faced by residents in each socio- economic context. The findings reveal shared challenges in both low and high-income areas, encompassing access to sanitation, clean air, healthcare, and civic engagement. However, the manifestations of these challenges differ; low-income neighborhoods experience more acute impacts on basic health and well-being, while high-income neighborhoods may grapple with issues related to the preservation of quality of life and efficient governance. This study contributes to the understanding of environmental health disparities and highlights areas for improvement in enhancing the overall well-being of residents in diverse urban settings. The research findings underscore the importance of targeted interventions tailored to the specific socio-economic context of neighborhoods in the City of Johannesburg. Additionally, the study emphasizes the relevance of Environmental Justice and Social Justice perspectives in addressing these disparities, thereby offering a comprehensive framework for future interventions.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Environmental Health; Socio-Spatial Disparities; Social Justice; Environmental Justice; SDG-11: Sustainable cities and communities; SDG-3: Good health and well-being